How do you factor c square plus 5c plus 6?

Would you like to merge this question into it?

already exists as an alternate of this question.

Would you like to make it the primary and merge this question into it?

exists and is an alternate of .

c2 + 5c + 6 = (c + 2)*(c + 3)
7 people found this useful

How can you factor- a squared plus b squared?

The sum of two squares cannot be factored. If that's -a^2 + b^2, that's b^2 - a^2, which factors to (b - a)(b+ a)

How do you factor x squared plus x plus 1?

That doesn't factor neatly. Applying the quadratic equation, we find two imaginary solutions: (-1 plus or minus the square root of -3) divided by 2. x = -0.5 + 0.8660254037844386 i x = -0.5 - 0.8660254037844386 i where i is the square root of negative one.

When you factor a squared plus ten a plus thirty what does it equal?

Hi, I'm not sure where you got this question, but it can't be factorised (using real numbers) as it has no real roots. The only solutions to this question are imaginary. (Don't worry about imaginary numbers unless you are in high school and doing the equivalent of ext. 2 maths in the NSW HSC (MORE)

How do you factor y squared plus 12y plus 35?

y2 + 12y + 35 = ( y + 7 ) ( y + 5 ) . Explanation: . You need to use a diamond equation, which looks like an X. The number 35 will go on the top of the X, and the 12 on the bottom. Now, you need to figure out what two numbers you can multiply together to get the top number as the result, (MORE)

How do you factor C squared plus C minus 56?

c^2 + c - 56 = (c - 7)(c + 8) using the factoring rule: c -7 -7c x x + c 8 8c c^2 -56 c

Factor x squared plus 35x plus 216?

For this problem, you may want to use the quadratic formula: x = (-b +or- sqrt(b 2 -4ac))/(2a) . where a and b are the coefficients in front of the x 2 and x terms, and c is the constant term. In this case, a = 1 b = 35 c = 216 . Now simply plug these values into the quadratic formula stated (MORE)

Factor X Squared plus 11x plus 24?

x 2 + 11x + 24You want the equation to be in the form (x + a)(x + b), where the two solutions are -a and -b. You know that... ab = 24 ...and... a + b = 11 Note that 8 times 3 is 24, and 8 plus 3 is 11. x2 + 11x + 24 = (x + 3)(x + 8) The two answers are x = -3 and x = -8.

Factor 2x squared plus 5x plus 3?

2x 2 + 5x + 3Notice the first term, which can be rewritten as 2x times x. With this in mind, you can write the equation as... (2x + a)(x + b) ...where -a and -b are the answers. You know that a times b is equal to 3. With a little trial and error, you will find: 2x 2 + 5x + 3 = (2x + 3)(x + 1)

What is the answer for x plus 6 squared?

Depending on whether or not there are implied brackets: x + 6 2 = x + 36 (x + 6) 2 = x 2 + 12x + 36

How do you factor z squared plus 7z plus 6?

The procedure for factoring z 2 +7z+6 is as follows: First, we must look at the number in front of the first variable. In this case, it is a 1. Then we look at the last number in the expression, which is a 6 (the expression must be arranged in descending order by the exponents of the variab (MORE)

C equals -3 4c plus 5c-2 equals?

When c = -3 then 4c + 5c - 2 = [4 x -3] + [5 x -3] - 2 = -12 +(-15) - 2 = -12 -15 -2 = -29

Factor c squared - 6cd plus 9d squared - 4?

c 2 - 6cd + 9d 2 - 4 The first three terms are a complete square = (c - 3d) 2 - 4 Difference of two squares = (c - 3d + 2)(c - 3d - 2)

Factor c squared plus 9d squared - 4?

Not sure if it can be done with the -4, but for the C sq +9D sq the answer would be C+3D. Hopes this helps!

What is the square root of 6 plus the square root of 6?

Square root of 6 = 2.44948 Sq root of 6 + Sq root of 6 = 2.44948 + 2.44948 = 4.89896

Factor 4x squared plus 8x plus 4?

4x 2 + 8x + 4 = 4 (x 2 + 2x + 1) = 4 (x + 1) 2

Factorization of 4x squared plus 12x plus 5?

The factors of 5 are 1 and 5. 12 = 2 x 5 + 2 x 1, therefore: 4x 2 +12x +5 = (2x + 1)(2x + 5) .

What is the force exerted on the -4 C by the plus 5C charge?

-4c charge can make the exerted force go on another object such as the 5c positive charge. because wen u multiply em' they make a similarity between them such as -4c+5c which equals to -c or -1c (same thing):)

How do you factor 3x plus 6?

3*x+6 common factor of 3&6 is 3 divide both terms by three: 3*x/3 --> x 6/3 --> 2 3(x+2)

What is 5c plus 15 equals 30?

5c + 15= 30 - 15 -15 5c = 15 If your solving for just c..... 5c/5 = 30/5 c= 3 Hope this helps adding further your question is incomplete you must ask for thevalue of C, since its a arithmetic equation.

How do you factor x squared plus 19x plus 90?

Factor as :. (x+9)(x+10). using the first terms ( x terms) multiply to x2; the last terms multiply to 90; the sum of 9x + 10 x = 19x.

What is 6x squared plus 5x minus 6 factored out to?

6x 2 + 5x - 6 is factored out to (2x + 3)(3x - 2).

12 equals 3c-12 plus 5c what is C?

3c - 12 + 5c = 12 Combine the 'c' terms on the left side: 8c - 12 = 12 Add 12 to each side: 8c = 24 Divide each side by 8: c = 3

What is A squared plus 6 squared equals 12 squared?

a 2 + 6 2 = 12 2 a 2 + 6 2 - 6 2 = 12 2 - 6 2 a 2 = 144 - 36 a 2 = 108 taking the square root of each side, we get a equal plus or minus the square root of 108, or plus or minus 6 times the square root of 3.

What is -5c plus 9 and how?

You can't tell a thing about -5c+9 until you know what 'c' is. And every time 'c' changes, -5c+9 changes.

What is the answer to 4x square plus 5x plus 6?

You haven't asked a question, so there's nothing there looking for an answer. 4x 2 + 5x + 6 is just a number. Its value depends on the value of 'x', and whenever 'x' changes, the value of this expression changes. If you had told us the value of this expression, then there would have be (MORE)

Explain how to factorize 2x squared plus 7x plus 6?

Your equation is a trimonial (made up of 3 parts) so your equation will end up being two sets of parentheses. In the first parentheses at the beginning goes the 2x, and at the begining of the second parentheses is x (because when you multiply 2x by x you get 2x^2 (two x squared) next you need to fin (MORE)

Factor x squared plus 4x plus 1?

It is not possible - you can't have two numbers that multiply to get one but add up to four

How do you factor 2u squared plus 13u plus 6?

I don't factor these. I am lazy, so I use the quadratic formula. -b +/- sqrt(b^2-4ac)/2a a = 2 b = 13 c = 6 u = - 13 +/- sqrt[13^2 - 4(2)(6)]/2(2) u = - 13 +/- sqrt(121)/4 u = [- 13 +/- 11]/4 u = - 1/2 u = - 6 My TI-84 confirms this answer. You check in original equation. (MORE)

How can you factor x squared plus 5x plus?

x 2 + 5x + not really sure what that extra plus is for... this is the most you can factor it... x(x + 5)

How do you factor c squared minus 7c plus 10?

To factor this equation... if you have learned before, find 2 numbers that add up to the middle value (-7) and multiply together to have a product of the last value (+10). You can use guess and check for this problem... but if you haven't already found it... the sum of -5 and -2 is -7... and the pr (MORE)

How do you factor 48x squared plus 139x plus 63?

48x 2 +139+63 = (3x+7)(16x+9) when factored and worked out with the help of the quadratic equation formula

What is x cubed minus 4x squared plus x plus 6 when fully factorized?

x 3 - 4x 2 + x + 6 = (x + 1)(x - 2)(x - 3)

How do you factor 9x squared plus 24x plus 16?

Let the symbol ^ mean "to the power" Then 9x^2 + 24x + 16 = (3x + 4)(3x +4) = (3x + 4)^2

How do you factor x squared plus 10y plus 25?

x 2 + 10y + 25 doesn't factor neatly. If that was x 2 + 10x + 25, it would factor to (x + 5)(x + 5) or (X + 5) 2

How do you factor 9x squared plus 27x plus 18?

Divide the entire equation by 9. (9x 2 + 27x + 18)/9 would then be 9(x 2 + 3x +2) The factors of this equation would be 9(x + 1)(x + 2)

How do you factor 4x squared plus 16x plus 5?

That doesn't factor neatly. Applying the quadratic formula, we findtwo real solutions: -2 plus or minus 0.5 times the square root of11. x = 0.3416876048223001 x = -3.6583123951777

How 20p squared plus 100p plus 125 factored?

20p 2 + 100p + 125 = 5(4p 2 + 20p + 25) = 5(4p 2 + 10p + 10p + 25) = 5(2p(2p + 5) + 5(2p + 5)) = 5(2p + 5)(2p + 5) = 5(2p + 5) 2

How do you factor 9x squared plus 3x plus 2?

It can't be factored because the discriminant of this quadratic expression is less than zero.

How do you factor 2x squared plus 11x plus 12?

2x 2 + 11x + 12 = 2x 2 + 3x + 8x + 12 = x*(2x + 3) + 4*(2x + 3) = (2x + 3)*(x + 4)

What is the factor of 3x squared plus 15x plus 6?

3x 2 + 15x + 6 = 3*(x 2 + 5x + 2). There are no further rational factors.

What is the answer for 5c plus 7 equals 23?

5c+7=23 -7 -7 5c=16 /5 /5 c= 3 & 1/5 or 16/5 thats really easy algebra 1 homework isn't it

What is the 3 coefficient of 5c plus 7m?

5 and 7 are two coefficient. And that is all. There is no third coefficient.

How do you factor x squared plus x plus 8?

That doesn't factor neatly. Applying the quadratic formula, we findtwo imaginary solutions: (-1 plus or minus the square root of -31)divided by 2. x = -0.5 + 2.7838821814150108 i x = -0.5 - 2.7838821814150108 i where i is the square root of negative one.

How do you factor d squared plus 4d plus 21?

That doesn't factor neatly. Applying the quadratic formula, we findtwo imaginary solutions: -2 plus or minus i times the squareroot of 17. x = -2 + 4.123105625617661 i x = -2 - 4.123105625617661 i where i is the square root of negative one.

How do you factor b squared plus 9b plus 2?

That doesn't factor neatly. Applying the quadratic formula, we findtwo real solutions: (-9 plus or minus the square root of 73)divided by 2. x = -0.2279981273412348 x = -8.772001872658766

How do you factor x squared plus 11x plus 30?

There's a factor pair of 30 that adds up to 11. (x + 5)(x + 6)

What are the factors of 6x squared plus 7x plus 6?

That doesn't factor neatly. Applying the quadratic formula, we findtwo imaginary solutions: (-7 plus or minus the square root of -95)divided by 12. x = -0.583333 repeating + 0.8122328620674136 i x = -0.583333 repeating - 0.8122328620674136 i where i is the square root of negative one.

How do you factor 18x squared plus 9x plus 2?

That doesn't factor neatly. Applying the quadratic formula, we findtwo imaginary solutions: (-1 plus or minus one third i timesthe square root of 7) divided by 4. x = -0.25 + 0.22047927592204922 i x = -0.25 - 0.22047927592204922 i where i is the square root of negative one.

How do you factor squared plus 1?

(x - i )(x + i) where i is the imaginary squareroot of negative one

What is a factor of 5x squared plus 13x minus 6 with work shown?

-6 = 3 x -2 13 = 5 x 3 - 2 â 5xÂ² + 13x - 6 = (5x - 2)(x + 3)